2020
DOI: 10.2105/ajph.2019.305440
|View full text |Cite
|
Sign up to set email alerts
|

Policy Determinants of Inequitable Exposure to the Criminal Legal System and Their Health Consequences Among Young People

Abstract: Criminalizing young people, particularly Black- and Brown-identified young people, has increasingly been a feature of US rhetoric, policies, and practices. Thus, the domains in which young people are exposed to the legal system have continued to expand, encompassing their communities, schools, and homes. Importantly, public health researchers have begun exploring links between legal system exposure and health, although this literature is primarily focused at the interpersonal level and assesses associations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 35 publications
2
37
1
Order By: Relevance
“…SROs are gatekeepers to the juvenile justice system. Youth are more likely to come in contact with the criminal legal system when there is an officer at their school, and this can have negative outcomes for their school connectedness (Theriot, 2016), educational attainment (Sweeten, 2006), positive development (Duarte et al, 2020), and legal future (Teske & Huff, 2011). Petteruti (2011) reported that schools with SROs arrest 3.5 times as many students as schools without SROs.…”
Section: The Promise Of Safe Schools At the Price Of Criminalizing Studentsmentioning
confidence: 99%
“…SROs are gatekeepers to the juvenile justice system. Youth are more likely to come in contact with the criminal legal system when there is an officer at their school, and this can have negative outcomes for their school connectedness (Theriot, 2016), educational attainment (Sweeten, 2006), positive development (Duarte et al, 2020), and legal future (Teske & Huff, 2011). Petteruti (2011) reported that schools with SROs arrest 3.5 times as many students as schools without SROs.…”
Section: The Promise Of Safe Schools At the Price Of Criminalizing Studentsmentioning
confidence: 99%
“…Aggressive policing practices are socially structured exposures [ 7 , 8 ] that can increase vulnerability to disease via stress pathways [ 20 ] linked to mental [ 20 ] and physical [ 21 ] health outcomes. In addition, these practices can also increase the risk of poor behavioral health outcomes such as excessive alcohol use to cope with the stress of a police-initiated contact [ 22 , 23 ]. Past analyses indicate that police stops and abuse are associated with poor mental, physical, and behavioral health outcomes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Public health researchers and practitioners, beyond those working in legal epidemiology, have long been concerned about the deleterious consequences of law enforcement practices on the public's health (Simckes et al 2021). For instance, it is now well documented that certain kinds of police encountersespecially ones that are aggressive or stigmatisingcan result in bad outcomes for physical and mental health (Geller et al 2014, Sewell and Jefferson 2016, Duarte et al 2020. Like medicine, policing can have 'iatrogenic' effects Burris 2017, Goulka et al 2021), producing harm and deepening inequalities (Rafla-Yuan et al 2021).…”
Section: Introductionmentioning
confidence: 99%